Translatio sanctitatis I furti di reliquie nell'Italia medievale - Marco Papasidero (Premio Istituto Sangalli per la storia religiosa, 2019)
This volume analyses the phenomenon of the thefts of sacred relics in Medieval Italy, in particular through the stealthy translationes, the hagiographic stories narrating the transfer of the relics from one place to another after they were stolen. Thanks to the study of historical contexts, narrative dynamics, literary themes and anthropological aspects, the book attempts to reconstruct the richness and complexity of the phenomenon over the centuries, tracing the history of this specific aspect of the cult of saints, which is also the history of the culture and religious imagery of the Middle Ages.